2011
DOI: 10.1093/ajae/aaq173
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Rural Firms Live Longer?

Abstract: Rural firms have a higher survival rate than urban firms. Over the first 13 years after firm entry, the hazard rate for firm exits is persistently higher for urban firms. While differences in firm attributes explain some of the rural-urban gap in firm survival, rural firms retain a survival advantage 18.5% greater than observationally equivalent urban firms. We argue that in competitive markets, the remaining survival advantage for rural firms must be attributable to unobserved factors that must be known at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…Single‐unit plants in metropolitan counties were 41 percent more likely to fail, even while controlling for county population, than those in remote rural counties (Table ). This result is in line with other studies examining survival and urban influence (Huiban ; Yu et al ). Yu et al find the hazard rate for urban firms was 18 percent higher than for rural firms in Iowa and 58 percent higher in Kansas.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Single‐unit plants in metropolitan counties were 41 percent more likely to fail, even while controlling for county population, than those in remote rural counties (Table ). This result is in line with other studies examining survival and urban influence (Huiban ; Yu et al ). Yu et al find the hazard rate for urban firms was 18 percent higher than for rural firms in Iowa and 58 percent higher in Kansas.…”
Section: Resultssupporting
confidence: 93%
“…Buss and Linn () point out that early work on survival rates in rural and urban areas suggests a rural disadvantage, but a growing body of evidence suggests the rural disadvantage has been over‐stated (Christie and Sjoquist ; Huiban ; Yu, Orazem, and Jolly ).…”
Section: Firm Survival Studiesmentioning
confidence: 99%
“…Stearns, Carter, Reynolds and Williams (1995) on the other hand find that rural firms have increased survival rates relative to urban firms. Similar results have been echoed by Yu, Orazem, and Jolly (2009) who found that rural firms have a 25 percent advantage for survival over their urban peers.…”
Section: Locationsupporting
confidence: 70%
“…Metropolitan regions naturally appear to be the more ideal location for start-up firms given the proximity to essential resources (Renski H. , 2008).One of the biggest challenges that rural start-ups face is access to capital, leaving them worse off relative to their urban peers who can more readily access and utilize capital to develop and grow their firms (Renski & Wallace, 2013). Rural firms also face the issue of asset fixity which requires a firm to have a higher probability of survival before entering a market given that the assets are less likely to be transferred to another firm and therefore, will have a lower salvage value or increased losses from failure relative to urban peers (Yu, Orazem, & Jolly, 2009). These issues dampen rural business development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation